(untitled) (Journal of Universal Science Research, 2024)
In strengthening the theme "Liquid and its properties", this competence is formed in the students by the constant temperature of spring water in winter and summer, its composition, feeding of fish living in the spring of dissolved minerals, in particular, the careful preservation of the rich heritage of our ancestors - the cultural and architectural complex "Chashma" in Nurata and following the rules of etiquette established there, kindness, generosity towards others, respect for the worldview, traditions and ceremonies of others.